A three-axial force sensor based on Fiber Bragg Gratings for surgical robots - Lai, Wenjie (2021)
Haptic feedback is absent in flexible endoscopic surgical robots due to the size constraint of installing sensors on the small robotic arms. Besides, inherent hysteresis caused by the nonlinear friction between tendons and sheaths makes it hard to estimate the distal force by modeling. In this work, we addressed this challenge by proposing a new three-axial force sensor. This standalone device can be seamlessly integrated into the endoscopic robotic arm. Three optical fibers with Fiber Bragg Gratings (FBGs) are embedded in the sensing structure, where one is located at the center hole of the structure (⌀ 1.4 mm), and the other two are eccentrically placed around the structure at 90° apart from each other. This device can measure the pulling force and lateral forces of an articulated surgical instrument. Mechanics analysis has been studied to reveal the link between FBGs’ wavelength shifts and forces caused by the elongation and the bending, with a temperature-compensation feature. The sensor has a lateral force sensitivity of 838.386 pm/N, with a measurement resolution of 1.19 mN. Performance comparison with a commercial force sensor Nano17 was made, with measurement errors from 4.50% to 6.18%. In the ex-vivo tests, we teleoperated the sensorized grasper to pull, steer and lift a piece of pig colon tissue. The tool-tissue interaction forces measured by the force sensor were displayed on the computer screen in real-time. In addition to the endoscopic robots, the force sensor can also be integrated with other surgical robots such as laparoscopic robots and catheters.